Manajemen Pendidikan Dasar dan Pengembangannya di SD Negeri 015 Muara Kaman - Aripin, Muhammad; Subaidah, Siti; Prihanto, Agus; Warman, Warman (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Management of basic education Improving the quality of administration in basic education institutions is crucial for the growth of elementary schools. One of the most important parts of education that contributes to better education is development. Institutional advancement is greatly aided by the improvement of basic education administration. Furthermore, the administration of basic education, which is integral to the school improvement procedure, is the purview of school development. Methods for gathering information in this descriptive qualitative study include interviews, observations, and written records. Findings from the study on basic education management now underway at SDN 015 Muara Kaman with the aim of raising the standard of education there, namely in two areas: first, the creation of curricula, and second, the implementation of those curricula.